Constraints on source parameters of the 25 April 2015, Mw = 7.8 Gorkha, Nepal earthquake from synthetic aperture radar interferometry - Sreejith, K. M.; Sunil, P. S.; Agarwal, Ritesh; Ramesh, D. S.; Rajawat, A. S. (My University, 2016)
We present InSAR observations of the co-seismic deformation caused by the Mw 7.8 Gorkha, Nepal earthquake. Analysis of Sentinel-1 data revealed about 100  100 sq. km surface deformation with ~1 m upliftment near Kathmandu, and ~0.8 m subsidence towards north along the line of sight of the satellite. The maximum deformation is observed about 40 km east–southeast of the epicentre, suggesting eastward propagation of the rupture. Elastic dislocation model-ling revealed that the overall rupture occurred on a 170 km long, 60 km wide fault along the strike (286) and dipping north (dip = 15) with large amount of slip (4.5 m) confined to the centre (95  22 sq. km) and less slip (0.25 m) on the surrounding part of the fault plane. The corresponding moment magnitude is Mw 7.75. The area, depth and dip of the modelled fault plane are fairly consistent and overlap with the loca-tion of mid-crustal ramp in the Main Himalayan Thrust. We infer that the earthquake was possibly caused by the release of inter-seismic strain energy accumulated in the environs of mid-crustal ramp due to plate boundary forces.
Keywords: Earthquake; Nepal earthquake; Co-seismic deformation; Gorkha; Synthetic aperture radar interferometry; Source model